Exploring the phase for highest impact on radicality: a cross-sectional study of patient involvement in quality improvement in Swedish healthcare. Issue 11 (8th November 2018) - Gremyr, Ida; Elg, Mattias; Smith, Frida; Gustavsson, Susanne
Abstract : Objectives: Involving patients in quality improvement is often suggested as a critical step for improving healthcare processes. However, this comes with challenges related to resources, tokenism, validity and competence. Therefore, to optimise the use of available resources, there is a need to understand at what stage in the improvement cycle patient involvement is most beneficial. Thus, the purpose of this study was to identify the phase of an improvement cycle in which patient involvement had the highest impact on radicality of improvement. Design: An exploratory cross-sectional survey was used. Setting and methods: A questionnaire was completed by 155 Swedish healthcare professionals (response rate 34%) who had trained and had experience in patient involvement in quality improvement. Based on their replies, the impact of patient involvement on radicality in various phases of the improvement cycle was modelled using the partial least squares method. Results: Patient involvement in quality improvement might help to identify and realise innovative solutions; however, there is variation in the impact of patient involvement on perceived radicality depending on the phase in which patients become involved. The highest impact on radicality was observed in the phases of capture experiences and taking action, while a moderate impact was observed in the evaluate phase. The lowest impact was observed in the identify and prioritise phase. Conclusions: Involving patients in improvement projects can enhance the quality of care and help to identify radically new ways of delivering care. This study shows that it is possible to suggest at what point in an improvement cycle patient involvement has the highest impact, which will enable more efficient use of the resources available for patient involvement.